Staged microsurgical treatment of a complex scalp arteriovenous fistula combined with type C sAVF and cirsoid aneurysm: a case report and literature review - Juncheng Wang; Juncheng Wang; Tao Kuai; Aichao Du; Lihua Yu; Yuzhen Duan; Guoqiang Yuan; Guoqiang Yuan; Dongming Ma; Yawen Pan; Yawen Pan (Frontiers in Oncology)
Scalp arteriovenous fistula (sAVF) is a rare disease caused by a congenital defect or exogenous injury, but no standard treatment exists. In this article, we report a rare case of sAVF combined with type C sAVF and cirsoid aneurysm (CA), which was successfully treated by staging microsurgery. Individualized surgical incisions were designed based on the size and range of the sAVF, and then staging microsurgery was performed. The first surgery was performed by selectively ligating the supply arteries and fistula of the sAVF. The second surgery was performed by total excision of the vascular malformation a month later. The volume of the vascular malformation in the subcutaneous area decreased after the first surgery, and the vascular malformation in the subcutaneous area was completely removed after the second surgery. In the end, we conclude that the nidus or fistula can be removed entirely through personalized surgical incisions for complicated sAVF combined with type C sAVF and CA.